2022
DOI: 10.1155/2022/5326355
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anticancer Potential of Biogenic Copper Oxide Nanoparticles (CuO NPs) against Breast Cancer

Abstract: The present study evaluated the anticancer potential of copper oxide nanoparticles (CuO NPs) synthesized from pumpkin seed extract in human breast cancer cell line (MDA-MB-231) using a battery of tests such as MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] assay, morphological alteration, reactive oxygen species (ROS) generation, and changes in mitochondrial membrane potential (MMP). The biogenic CuO NPs showed a dose-dependent decline in cell viability with 50% inhibitory concentration (IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 49 publications
4
25
0
Order By: Relevance
“…Many reports were documented on the appropriateness and suitability of ASO to prepare biodiesel using different catalysts. However, the physicochemical properties of ASO observed from this study have well supported with the results reported by Kaur et al [17]. Thus, the reliability and viability of obtained ASO were ensured for the further esterification process.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Many reports were documented on the appropriateness and suitability of ASO to prepare biodiesel using different catalysts. However, the physicochemical properties of ASO observed from this study have well supported with the results reported by Kaur et al [17]. Thus, the reliability and viability of obtained ASO were ensured for the further esterification process.…”
Section: Resultssupporting
confidence: 90%
“…In order to evaporate the additional solvent, water bath was used and excess solvent (n-hexane) was removed at 70 °C. Because of the oil has less volatility, they can retain in the experimental flask [17]. The extracted oil was observed to be golden yellowish color.…”
Section: Preparation Of Asomentioning
confidence: 99%
“…The masking of positive charge on lysine and arginine by nanoparticles, considered as inhibitory action of nanoparticles 9 . Since over the last few years, researchers showing their interest in searching better disease preventing agents from plant derived phenolic and other bioactive compound to plant‐based bio‐synthesized nanoparticles 54‐58 . To confirm the antiglycating property of TNP, together with inhibitory protein modification action, the reduction in the ketoamine, carbolnyl content and AGEs formation observed in our study confirmed the efficacy of the antiglycation effect of plant based TNP.…”
Section: Resultssupporting
confidence: 81%
“…9 Since over the last few years, researchers showing their interest in searching better disease preventing agents from plant derived phenolic and other bioactive compound to plant-based biosynthesized nanoparticles. [54][55][56][57][58] To confirm the antiglycating property of TNP, together with inhibitory protein modification action, the reduction in the ketoamine, carbolnyl content and AGEs formation observed in our study confirmed the efficacy of the antiglycation effect of plant based TNP. Although, TNP mechanism of action is not very clear and understood; hence, its inhibitory mechanism against the glycation is a matter of further investigation.…”
Section: Ans-hydrophobicity Change Detection By Fluorescence Spectrasupporting
confidence: 78%
“…The nanotechnology-based formulation has shown improved stability and biocompatibility, enhanced permeability and retention effect, and precise targeting to cancer sites ( Kim et al, 2021 ; Sharifi-Rad et al, 2021 ). Among the various nanoformulations, the use of metal oxide nanoparticles in preventive medicine has risen due to their unique physicochemical characteristics, such as high surface/volume ratio, broad optical properties, ease of synthesis, surface functionalization, cost effectiveness, and environment-friendly nature ( Tabrez et al, 2022b ; Zughaibi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%